History of patronage relations formation in Ukraine - Liubov Fushtei (Vasyl Stefanyk Precarpathian National University, 2017)
The article analyzes the concepts of "patronage" and "foster family". The necessity tointroduce patronage relations and foster care in modern Ukraine is revealed. The history ofpatronage relations in Ancient Rome, the Russian empire and the Soviet Ukraine of 20-30thcentury is given. Key words: patronage, guardianship, foster family, foster care, history of patronagerelations in Ukraine.